Types of green practices, hotel price image and consumers' attitudes in China: the mediating role of consumer skepticism. Issue 3 (2nd April 2020) - Yin, Cheng-Yue; Du, Fan; Chen, Yong
ABSTRACT: This study demonstrates the interaction effect of hotel green practices and price image on consumers' skepticism and attitudes toward hotels. When hotels adopt green practices with hotel cost reductions, consumers' skepticism toward hotels with a low price image is higher than their skepticism toward hotels with a high price image, and their attitude toward the former is more negative. When hotels adopt green practices with customer cost reductions, consumers' skepticism toward hotels with a low price image is lower than their skepticism toward hotels with a high price image, and their attitude toward the former is more positive. When green practices with increasing customer cost are adopted, consumers' skepticism toward hotels with a low price image is higher and their attitude is more negative compared to hotels with a high price image. These findings suggest that hotels must carefully consider the combination of green practices with their price image.